KEARIFAN OKOMAMA SEBAGAI SARANA MEDIASI DALAM PENYELESAIAN KONFLIK TANAH ULAYAT (Studi Kasus Penyelesaian Konflik Tanah Ulayat Adat Di Desa Noinbila Kecamatan Mollo Selatan Kabupaten Timor Tengah Selatan) - Fay , David Mariano; Servatius, Rodriques; Ola, Urbanus (Yayasan Panca Bakti Wiyata Pangandaran, 2026)
Customary land for indigenous communities has diverse economic, political, cultural, and spiritual meanings, so that conflict can disrupt social harmony and community identity. Disputes over customary land in Noinbila often arise due to differing ownership claims between managers and owners, which are usually based only on verbal agreements without official documents. In this case, the community prefers to use customary methods through Okomama rather than resolving disputes through formal law. Okomama serves as a place for customary deliberation, where mediators appointed by customary leaders bring peace symbols such as betel nut, sopi, and money as a sign of willingness to reconcile. This research uses a case study approach with qualitative methods, through interviews, observations, and document collection from customary leaders, the community, and related parties. The results of the study indicate that Okomama is effective as a means of mediation based on tradition in mitigating conflict, strengthening social solidarity, and contributing to the development of social science, customary law, and public policy regarding customary land management. These findings emphasize the significance of preserving local wisdom as a sustainable strategy for conflict resolution amidst the modernization process. Customary land for indigenous communities has diverse economic, political, cultural, and spiritual meanings, so that conflicts can disrupt social harmony and community identity. Disputes over customary land in Noinbila often arise due to differing ownership claims between managers and owners, which are usually based only on verbal agreements without official documents. In this case, the community prefers to use customary methods through Okomama rather than resolving them through formal law. Okomama functions as a place for customary deliberation, where mediators appointed by customary leaders bring peace symbols such as betel nut, sopi, and money as a sign of willingness to reconcile. This research uses a case study approach with qualitative methods, through interviews, observations, and document collection from customary leaders, the community, and related parties. The results of the study indicate that Okomama is effective as a means of mediation based on tradition in reducing conflict, strengthening social solidarity, and contributing to the development of social sciences, customary law, and public policy regarding customary land management. This finding emphasizes the significance of preserving local wisdom as a sustainable strategy in resolving conflicts amidst the modernization process.